Few‐layer graphene doped with boron to enhance ammonium hydroxide vapour detection at low temperature. (1st March 2018) - Ahmadi, Shahrokh; Afzalzadeh, Reza
Abstract : Few‐layer graphene and multilayer graphene are grown using atmospheric pressure chemical vapour deposition method with polystyrene as a solid carbon source on copper foil. These experimentations demonstrate that the sensor made of few layer graphene compared to multilayer graphene shows 12.5 times higher sensitivity to the vapour of ammonium hydroxide. Doping of a few layer graphene by boron is done by using boric acid as a solid precursor. The sensitivity of the few layer graphene sensor after 20 min has increased by 4.7 times when the graphene layer was doped with boron atoms (∼2.1%) for ammonium hydroxide detection. Selectivity of the boron doped sensor for ammonium hydroxide is about 16 times more than the presence of ethanol and methanol vapours. All measurements were done at room temperature and in air ambient. Atomic force microscopy, X‐ray photoelectron spectroscopy and Raman spectroscopy have been used for characterisation of the layers. The dynamic response of the sensor is well fitted with Freundlich isotherm.